2017
DOI: 10.1002/cncr.30635
|View full text |Cite
|
Sign up to set email alerts
|

Reduced rate of human papillomavirus infection and genetic overtransmission of TP53 72C polymorphic variant lower cervical cancer incidence

Abstract: BACKGROUNDCervical cancer is a predominantly human papillomavirus (HPV)‐driven disease worldwide. However, its incidence is unexplainably low in western Asia, including Saudi Arabia. Using this paradigm, we investigated the role of HPV infection rate and host genetic predisposition in TP53 G72C single nucleotide polymorphism (SNP) presumed to affect cancer incidence.METHODSPatients treated between 1990 and 2012 were reviewed, and a series of 232 invasive cervical cancer cases were studied and compared with 313… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Overall, these results imply that the prevalence of HPV-driven HNSCC in our population is very low. The reasons for this low rate is unknown, but could be related to the predominance of other risk factors, such as various tobacco products consumption, which is as high as 62% of patients, socio-cultural differences, or the presence of relative protective variants of genetic predisposing factors as has been shown previously for cervical cancer patients [31]. Most infections (90%) were with HPV16 (9/10) followed by 10% with HPV33 (1/10) genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these results imply that the prevalence of HPV-driven HNSCC in our population is very low. The reasons for this low rate is unknown, but could be related to the predominance of other risk factors, such as various tobacco products consumption, which is as high as 62% of patients, socio-cultural differences, or the presence of relative protective variants of genetic predisposing factors as has been shown previously for cervical cancer patients [31]. Most infections (90%) were with HPV16 (9/10) followed by 10% with HPV33 (1/10) genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This PCR-based test detects and genotypes the 37 most common anogenital HPVs (13 high-risk: 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 68, and 24 low-risk: 6, 11, 26, 40, 42, 53, 54, 55, 61, 62, 64, 66, 67, 69, 70, 71, 72, 73 (MM9), 81, 82 (MM4), 83 (MM7), 84 (MM8), 89 (CP6108) and IS39). Procedures followed the manufacture’s instruction described in detail previously [31,49]. Briefly, the methodology involves the PCR amplification of the target DNA, the hybridization of the amplified DNA segments to oligonucleotide probes immobilized on strips of membranes, and finally, the colorimetric detection of the hybridized products using the Linear Array Detection Kit.…”
Section: Methodsmentioning
confidence: 99%
“…These findings have been collaborated with the meta-analysis study which reported that Pro/Pro genotype and proline allele was associated with increased risk of cervical cancer within the Indian population [ 21 ]. On the contrary, the proline allele was found to confer a protective effect in patients with cervical cancer from Saudi Arabia [ 22 ]. The proline allele has also been linked with increased overall survival in Caucasian cervical cancer patients [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies have been performed to assess the effect of SNPs on cervical cancer susceptibility [1113]. Based on these reports and findings from bioinformatics studies exploring high risk factors within the Chinese population for cervical cancer, we focused our current study on crucial genes within the DNA repair and recombination pathways.…”
Section: Introductionmentioning
confidence: 99%